Analysis of Economic Development Planning on Human Development - Rifqah Harahap; M. Asbullah; Indra Ismayudi Tanjung; Liasulistia Ningsih; Mutiara Shifa (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The purpose of this study is to examine the conceptual analysis of economic development planning to human development. The conceptual analysis in this study aims to provide an in-depth explanation of economic development planning to human development, using secondary data in the form of related books and journal articles. The research results from a conceptual analysis perspective show that economic development planning to human development shifts the focus of the development paradigm from capital-centric, oriented toward capital accumulation and gross domestic product growth, to human-centric, oriented toward expanding human capabilities and well-being. Economic development planning is an instrument of socio-economic engineering, while human development is its moral compass and ultimate goal. A well-thought-out development plan rejects the assumption that economic growth automatically trickles down. Instead, it consciously invests economic capital into human capital, creating a virtuous cycle in which qualified people will drive much stronger, innovative, and sustainable economic growth.